Kinetic analysis of antagonist-occupied adenosine-A3 receptors within membrane microdomains of individual cells provides evidence of receptor dimerization and allosterism - Corriden, Ross; Kilpatrick, Laura E.; Kellam, Barrie; Briddon, Stephen J.; Hill, Stephen J. (Federation of American Society of Experimental Biology, 2014)
In our previous work, using a fluorescent adenosine-A3 receptor (A3AR) agonist and fluorescence correlation spectroscopy (FCS), we demonstrated high-affinity labeling of the active receptor (R*) conformation. In the current study, we used a fluorescent A3AR antagonist (CA200645) to study the binding characteristics of antagonist-occupied inactive receptor (R) conformations in membrane microdomains of individual cells. FCS analysis of CA200645-occupied A3ARs revealed 2 species, τD2 and τD3, that diffused at 2.29 ± 0.35 and 0.09 ± 0.03 μm2/s, respectively. FCS analysis of a green fluorescent protein (GFP)-tagged A3AR exhibited a single diffusing species (0.105 μm2/s). The binding of CA200645 to τD3 was antagonized by nanomolar concentrations of the A3 antagonist MRS 1220, but not by the agonist NECA (up to 300 nM), consistent with labeling of R. CA200645 normally dissociated slowly from the A3AR, but inclusion of xanthine amine congener (XAC) or VUF 5455 during washout markedly accelerated the reduction in the number of particles exhibiting τD3 characteristics. It is notable that this effect was accompanied by a significant increase in the number of particles with τD2 diffusion. These data show that FCS analysis of ligand-occupied receptors provides a unique means of monitoring ligand A3AR residence times that are significantly reduced as a consequence of allosteric interaction across the dimer interface